Potential carbon sequestration in a Mediterranean organic vegetable cropping system. A model approach for evaluating the effects of compost and Agro-ecological Service Crops (ASCs). (May 2018) - Farina, Roberta; Testani, Elena; Campanelli, Gabriele; Leteo, Fabrizio; Napoli, Rosario; Canali, Stefano; Tittarelli, Fabio
Abstract: Organic farming relies, for soil fertility management, on proper rotation designs, Agro-ecological Service Crops (ASCs) and a sound use of on- and off-farm organic inputs. The right combination of soil fertility factors in organic farming is essential to enhance soil organic C (SOC) sequestration. A field trial experiment was overlaid on an long term organic farming experiment, in Monsampolo del Tronto (42° 53′ N, 13° 48′ E) in Central Italy, based on a 4-years rotation, with 6 main crops, and 3 different ASCs. The treatments included: i) the alternative termination of the cover crop (barley) with roller crimper technique compared to green manure and ii) the application of compost (not applied before) in different doses. The barley managements were: green manure (GMB); flattened (FB) by the use of a roller crimper; no barley (NB) as control. The compost (Cp) doses were: 0, 15 and 30 Mg C ha −1 to study the effect on soil C dynamics of compost application and ASCs termination techniques. The historic and experiment results were used as input to run a soil C dynamics model (RothC10N) to predict the effect of the factors different combinations in a medium term (20 years). After two years from compost application, the SOC stock increased in all plots, by +1.8, +2.3 and +4.9 Mg C ha −1 for Cp0, Cp15 and Cp30 respectively, compared to the initial stock of 36.8 Mg ha −1 . The effect of different ASCs termination and ASC × compost interaction was not statistically significant. The RothC10N model was used to predict the effect of ASCs (NoASCs, FB and GMB) and Cp doses in a 20 years period. Predictions of the calibrated and validated RothC10N model showed that SOC change in 20 years was negative in the scenario with no ASCs-no compost (NoASC Cp0), where the C inputs were not sufficient to offset C losses, whereas positive values were predicted for all the other scenarios. The average values of predicted C stock change in 20 years were 3.8, 13.3 and 19.8 Mg C ha −1 for NoASC, FB, and GMB respectively and 8.2. 12.2 and 16.5 Mg C ha −1 . for Cp0, Cp15 and Cp30. Both field experiment and model showed that the green manure of ASC and compost application represent a valid option in terms of carbon sequestration increase. RothC10N model can be used successfully as a tool to compare the C sequestration potential of alternative agronomic practices. Highlights: We modeled soil carbon dynamics in a Mediterranean organic vegetable cropping system. RothC10N simulated well soil carbon change after compost addition and different cover-crops termination techniques. Cover-crops and compost are able to increase the soil C content in the long term in organic farming systems. The methodology is a tool for scientists and policy makers to identify management options for C sequestration.